HUMOR SUBVERSIF DALAM VIDEO MUSIK BALANCE TON QUOI OLEH ANGELE - Zarkasya, Nur Annisa Khalish; Miranda, Airin (UI Scholars Hub, 2025)
The phenomenon of the #MeToo and #BalanceTonPorc hashtags became the focus of attention in various parts of the world in 2017. It was first popularized by Alyssa Milano on her Twitter account using the #MeToo hashtag, and later followed by Sandra Muller with #BalanceTonPorc in France. The feminist movement on social media inspired many artists and musicians, including Angèle, a singer from Belgium. She released a song and music video titled